Dielectric relaxation in AC powder electroluminescent devices - Zhang, Shuai (2016)
The dielectric properties of AC powder electroluminescent devices were measured and analyzed using complex impedance spectroscopy to determine the relaxation processes occurring within the devices. The relaxation processes identified were ascribed to the electrode polarization caused by ion accumulation at the electrode/resin interfaces, the Maxwell-Wagner-Sillars effects at the (ZnS or BaTiO3) particle/resin interfaces, and the dipolar reorientation of polymer chains in the resin matrix. Each relaxation process was represented by its corresponding equivalent circuit component. Space charge polarization at the electrodes were represented by a Warburg element, a resistor, and a constant phase element. The resin matrix, ZnS/resin and BaTiO3/resin interfaces could each be modeled by a resistor and a capacitor in parallel. The simulated equivalent circuits for three different printed structures showed good fitting with their experimental impedance results.